Problematyka patriotyzmu w wychowaniu harcerskim w Związku Harcerstwa Rzeczypospolitej (ZHR) - Kołodziej, Anna (Biuletyn Historii Wychowania, 2013)
The historical education of youth has played an important role in patriotic education. The results of academic research into the patriotism of Polish youth shows the growing need of patriotic education in the context of situating patriotism as an independent category, an element of the axiological system, the awareness of Polish youth. The analysis of contemporary Polish reality indicates new challenges in patriotic education. With the ZHR we are dealing with a specific vision of our history, as well as a specific version of present times and a specific cultural code. Scouting is considered an organization that has become an inherent part of Polish tradition and culture, and the ideal of being raised in the scouting tradition has been stablished in the consciousness of a number of generations of Poles. It is a consequence of our national culture and tradition. Scouting has been used as a tool for developing an independent attitude amongst patriotic youths. It also became an essential part of the struggle for independence. Scouting as a system of education has been subject to change and ongoing development in changing socio-political and economic conditions. This process has continued in the contemporary, postmodern and post-industrial society. Patriotic education in scouting is an element of scouting methodology based on Scouting Law and the Scouting Oath.